2006
DOI: 10.1002/neu.20276
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the level of Bcl-2 family proteins and caspase-3 activation in the sexually dimorphic nuclei of the preoptic area in postnatal rats

Abstract: In developing rats, sex differences in the number of apoptotic cells are found in the central division of the medial preoptic nucleus (MPNc), which is a significant component of the sexually dimorphic nucleus of the preoptic area, and in the anteroventral periventricular nucleus (AVPV). Specifically, male rats have more apoptotic cells in the developing AVPV, whereas females have more apoptotic cells in the developing MPNc. To determine the mechanisms for the sex differences in apoptosis in these nuclei, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 36 publications
(55 reference statements)
3
53
0
Order By: Relevance
“…It is also consistent with work of others who found higher levels of Bcl2 protein in the AVPV of developing females (10). Our in vitro data show that TNF␣ increases both NFB p65 subunits and Bcl2 gene expression in N42 cells and that TRIP inhibits both.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It is also consistent with work of others who found higher levels of Bcl2 protein in the AVPV of developing females (10). Our in vitro data show that TNF␣ increases both NFB p65 subunits and Bcl2 gene expression in N42 cells and that TRIP inhibits both.…”
Section: Discussionsupporting
confidence: 81%
“…Previous work similarly demonstrated that Bax protein levels are higher in male AVPV, but that work found no differences in Bad protein levels (10). An important finding in our studies was that, unlike bcl2, neither bax nor bad gene expression was regulated by TNF␣ or TRIP.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…These differences may be due to a differential balance in the expression of members of the antiapoptotic family of Bcl-2 genes, and those in the pro-apoptotic family of Bax family genes. Male and female mice with mutations to these genes have significant changes in neuron numbers in the AVPV and SDN-POA, and there are natural sex differences in the expression of apoptotic genes in wildtype animals [172,53,157]. More specifically, deletion of Bax (proapoptotic) abolished sex differences in AVPV cell numbers [53], and overexpression of Bcl-2 (anti-apoptotic) had a similar effect [172].…”
Section: Mechanisms For Hormone Effects On Avpv and Sdn-poa Morphologymentioning
confidence: 99%
“…Supporting this hypothesis are the studies demonstrating dimorphism in the expression of pro-and anti-apoptotic proteins, Bax and Bcl-2, respectively, in structurally dimorphic brain regions [85,86]. Moreover, both overexpression of anti-apoptotic proteins or deletion of pro-apoptotic genes in brain have been shown to eliminate structural sex differences [87,88].…”
Section: Same Histone Modifications Results In Sexually Dimorphic Braimentioning
confidence: 91%